ENHANCING CLIMATE RESILIENCE AND FOOD SECURITY IN MUDZI RURAL DISTRICT THROUGH INTEGRATED WATERSHED MANAGEMENT AND CONSERVATION AGRICULTURE - Gudyani, Shepherd; Matunhu, Jephias; Mabiza , Hilda Jaka (The journal of contemporary issues in business and government, 2025)
Agriculture constitutes the cornerstone of Zimbabwe's rural economy, providing sustenance and driving economic activities for most rural populations. However, despite its significance, rural agriculture has increasingly faced multifaceted challenges, including climate change and the failure to implement context-specific improvement strategies, leading to noticeable decline. This decline has caused widespread food insecurity, prompting a surge in donor-assisted food aid programs across rural Zimbabwe since 2016, mostly affecting rural communities that are heavily reliant on agricultural commodities for food, income, employment, and market access. Nevertheless, despite the apparent collapse of rural agriculture, prospects for sustenance and resilience remain alive. This paper argues that tailored approaches such as integrating Watershed Management and Conservation Agriculture can revitalize rural agriculture and bolster food security. By integrating Watershed Management and Conservation agriculture strategies, rural communities can reclaim agriculture as a vital component of their economy and mitigate the pervasive food insecurity that has been pervasive for years. This paper explored integrating Watershed Management practices into Conservation Agriculture to enhance adaptability, productivity, resilience and food security in rural communities; while providing a strategic response to climate change shocks, especially responding to climate change rainfall disruptions, seasonal changes, crop and livestock diseases and low crop productivity. This article stems from a PhD study, “Towards rural household food security through investment in productive assets (PA): A case of Mudzi Rural District in Zimbabwe”, in which the study employed a qualitative methodology, comprising five focus group discussions involving fifty-two community members, field observations, eighteen key informant interviews, thirty-five majorly qualitative questionnaires, literature review, and a case study of Mudzi district. This paper reveals that the two approaches are mutually compatible and integrating them can synergistically assist to transform rural agriculture, bolstering food security and climate resilience in Zimbabwe.